ANALISIS PENGARUH KEBIJAKAN REMUNERASI TERHADAP GOOD GOVERNANCE DI TANGERANG SELATAN - Endang Ruhiyat (Universitas Pamulang, 2014)
Remuneration Policy Influence Analysis Of Good Governance in South Tangerang.This study aims to determine the effect on the remuneration practices of good governance. This study is associative. The sample was three government agencies that are in the region of South Tangerang City Government, namely the Ministry of Research and Technology, Ministry of Education and Culture, and the Ministry of Environment. The sampling technique was convenience sampling is done to assure proportional allocation based sample represents all South Tangerang City Government institutions. Remuneration policy is measured using a Likert scale. While the remuneration indicators used in this study are: Fair, Encouraging Motivation, Competitive, Right, and Compliance Provisions Act and applicable government regulations. Good governance is measured using a Likert scale. While the indicators used in this study refers to Duncan, et al as follows: Rule of Law Index, Government Effectiveness Index, Index of Social Development, and Regulatory Quality Index. Analysis method using simple regression analysis. Based on the results obtained it can be concluded that the evidence supporting the positive effects of increasing the remuneration policy of good governance. Keywords: Remuneration, Good Governance.